Does having an asthmatic sibling affect the quality of life in children? - Özge Yılmaz; Ahmet Türkeli; Özlem Karaca; Hasan Yüksel (The Turkish Journal of Pediatrics)
Chronic illness in a family member leads to deterioration of quality of life in other members of that family. We aimed to investigate the influence of having an asthmatic sibling on a child`s quality of life (QoL). We enrolled 2-12 year aged healthy children with an asthmatic sibling in the study group and healthy children with a healthy sibling in the control group of this cross-sectional study. Sociodemographic characteristics of children and disease severity characteristics of asthmatic siblings were recorded. All parents filled in Turkish generic PedsQLTM short form appropriate for the child`s age group. Study and control groups had 114 children each. Total PedsQLTM scores were not significantly different in any of the age groups (p=0.23, p=0.13, p= 0.11 respectively). Emotional PedsQLTM sub-scores in children with an asthmatic sibling were significantly worse (83.0±16.5 vs 91.6±10.9 in the 2-4 year age group, 72.0±17.8 vs 92.2±11.6 in the 5-7 year age group, 73.7±24.1 vs 88.7±14.8 in the 8-12 year age group respectively, p≤0.002 for all). Similarly, psychosocial sub-score was significantly lower in the 2-4 and 5-7-year-olds but not the 8-12 year old groups (p=0.01, p=0.01, p=0.08 respectively). In conclusion, healthy children with asthmatic siblings have significantly lower emotional QoL and this needs to investigated for other chronic diseases in further research.